Tribological performance of low viscosity halogen-free ammonium based protic ionic liquids with carboxylate anions as neat lubricants - Al Kaisy, G.M.J. (Elsevier Ltd, 2021)
The tribological performance of six low viscosity, hydrophobic, halogen- sulfur-, and phosphorous free trioctylammonium-based protic ionic liquids with 2-naphthoate, 4-tert-butylbenzoate, 2-hexyldecanoate, 4-phenylbutanoate, 3,4-dimethylbenzoate, and salicylate anions were studied as lubricants for steel-steel interfaces using a four-ball tribo-tester. The results showed a significant friction reduction up-to 28 Ì¶ 65 compared to polyalphaolefin lube base oil. Where the salicylate protic ionic liquid showed the lowest coefficient of friction. In terms of wear, the 2-naphthoate and salicylate protic ionic liquids exhibited wear scar diameter values lower than polyalphaolefin by 4.7 and 0.42, respectively. The scanning electron microscopy and X-ray photoelectron spectrometer analysis outcomes of the wear scar surfaces indicated that tribo-chemical reactions were involved among the protic ionic liquid molecules and the steel surfaces during the tribo-test, developing a protective boundary film, which contributed significantly to the lubrication performance of the protic ionic liquidsâ lubricants. No corrosion was observed for the copper strip corrosion test carried out to examine the corrosion characteristics of the studied protic ionic liquids. The overall results confirm the high capability of applying this group of protic ionic liquids as lubricants. Â© 2021 Elsevier Ltd